Early Right Ventricular Apical Pacing-Induced Gene Expression Alterations Are Associated with Deterioration of Left Ventricular Systolic Function. (8th August 2017) - Xu, Haiyan; Xie, Xiongwei; Li, Jiangjin; Zhang, Yuanyuan; Xu, Changsong; Yang, Jing
Abstract : The chronic high-dose right ventricular apical (RVA) pacing may have deleterious effects on left ventricular (LV) systolic function. We hypothesized that the expression changes of genes regulating cardiomyocyte energy metabolism and contractility were associated with deterioration of LV function in patients who underwent chronic RVA pacing. Sixty patients with complete atrioventricular block and preserved ejection fraction (EF) who underwent pacemaker implantation were randomly assigned to either RVA pacing (n = 30 ) group or right ventricular outflow tract (RVOT) pacing (n = 30 ) group. The mRNA levels of OPA1 and SERCA2a were significantly lower in the RVA pacing group at 1 month's follow-up (both p < 0.001 ). Early changes in the expression of selected genes OPA1 and SERCA2a were associated with deterioration in global longitudinal strain (GLS) that became apparent months later (p = 0.002 and p = 0.026, resp.) The altered expressions of genes that regulate cardiomyocyte energy metabolism and contractility measured in the peripheral blood at one month following pacemaker implantation were associated with subsequent deterioration in LV dyssynchrony and function in patients with preserved LVEF, who underwent RVA pacing.